Importance of ethics of public officials (2016)
Public officials have a great responsibility because their efforts are dedicated the benefit of society through state entities and for this very reason are monitored by the control entities as well as by the observers and people in general, these reasons public officials should perform their duties according to a strict code of ethics which are specified from the attitudes of service to others that should have up their duties, they should also take into account the possible offenses that may be incurred as by omission or mistakes in their actions they can be judged by the judicial authorities.